Folkloric communication as a modus of the semiotic system (Literatures of the World: Poetics, Mentality and Spirituality, 2017)
The headline of the article is “Folklore Communication as modus semiotic system”. The article devotes considerable attention to folklore as communication proses. The article considers functions of folklore communication. It must be stressed that in this article author proposes to distinguish the intertextual function. It is of importance to note that folklore communication has such levels: interpersonal and interethnic community. Folklore communication is model of semiotic act and component of a complex semiotic system. Folklore communication refers to the indirect, therefore absence of contact between the performer and the listeners.
Keywords: folklore; folklore communication; interethnic communication; intertextual function; semiotic act; semiotic system; interethnic polylogue